2021
DOI: 10.1186/s12885-021-09002-0
|View full text |Cite|
|
Sign up to set email alerts
|

No differences in the long-term prognosis of iris and choroidal melanomas when adjusting for tumor thickness and diameter

Abstract: Objective To assess the long-term prognosis for patients with iris melanomas and compare it with the prognosis for small choroidal melanomas. Design Retrospective observational case series. Methods All patients treated for iris melanomas at a single referral institution between January 1st 1986 and January 1st 2016 were included. Patients treated for small choroidal melanomas during the same period wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The recent observation of a 80–90% metastatic rate among patients with untreated primary tumors indicates that a beneficial effect might exist after all ( 9 ). This may be further corroborated by the observation that there are no survival differences between melanomas originating in the choroid or the iris when adjusting for tumor size, although additional studies are needed to verify this observation ( 34 ). The reason for the relatively good prognosis in iris melanoma is likely that they are typically diagnosed at a small size.…”
Section: Discussionmentioning
confidence: 78%
“…The recent observation of a 80–90% metastatic rate among patients with untreated primary tumors indicates that a beneficial effect might exist after all ( 9 ). This may be further corroborated by the observation that there are no survival differences between melanomas originating in the choroid or the iris when adjusting for tumor size, although additional studies are needed to verify this observation ( 34 ). The reason for the relatively good prognosis in iris melanoma is likely that they are typically diagnosed at a small size.…”
Section: Discussionmentioning
confidence: 78%
“…We have previously shown that patients presenting with a shadow in the visual field have significantly shorter disease‐specific survival, regardless of other symptoms, tumour size, location, local extent and stage (Fili et al, 2020 ). In turn, tumours from UM patients that report a visual field shadow are more likely to display vasculogenic mimicry and greater density of PAS positive patterns, which may underpin the association between this symptom and poor prognosis (Sabazade et al, 2021a , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…One exception is a large study by Kujala et al ( 2013 ), who found that tumour diameter, tumour thickness, CBI and extraocular extension were all independent predictors of melanoma‐related mortality in multivariate Cox regression (Kujala et al, 2013 ). In contrast to iris melanomas who have no better prognosis than choroidal melanomas when adjusting for tumour diameter and thickness, this should make it unlikely that increased tumour size is the real reason for the prognostic implication of CBI (Johansson et al, 2020 ; Sabazade et al, 2021a , 2021b ). The American Joint Committee on Cancer (AJCC) classification of UM consequently assigns tumours with CBI a subcategory with shorter metastasis‐free survival (Kujala et al, 2013 ; Kujala & Kivela, 2005 ; Simpson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 15-year melanoma-specific survival in Scotland is 83.8%, 81.3%, and 100% for choroidal, ciliary body, and iris melanomas, respectively [3]. Fifteen-year survival for in Sweden for choroidal and iris melanomas has been reported as 84% and 92%, respectively [4], and 5- and 10-year melanoma-specific survival figures for choroidal melanoma in the USA have been reported as 87% and 78.5% [5], respectively.…”
Section: Introductionmentioning
confidence: 99%